1991
DOI: 10.1002/pssb.2221670222
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Cu and Ni Band Structure above the Vacuum Level Using Low Energy Electron Reflection

Abstract: Incidence angle dependent elastic electron reflection curves in the 0 to 30 eV range are measured on Cu(ll1) and Ni(ll1) using target current regime. They are compared with the calculated ones. Computations are made very fast using a simple approximation. The extrema of the reflection energy derivative are shown to correspond unambigiously to definite critical points of bands. These points are mapped when the energies of the experimental extrema are compared with the calculated ones. Varying the incidence angl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

1992
1992
1997
1997

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 12 publications
(5 reference statements)
0
25
0
Order By: Relevance
“…This masking may be understood analysing the Fourier expansion of wave functions. Near any of these points the Bloch function is the sum of plane waves exp (i(k + C ) v) that did not contain any "conducting" component [6] associated with the primary plane wave exp ( X v ) (this component is discriminated by its k l l + Gll being equal Kll). In this case matching of wave functions on the surface [2] gives no excitation of this Bloch function and the associated CP cannot manifest itself.…”
Section: Construction Of Bands and Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This masking may be understood analysing the Fourier expansion of wave functions. Near any of these points the Bloch function is the sum of plane waves exp (i(k + C ) v) that did not contain any "conducting" component [6] associated with the primary plane wave exp ( X v ) (this component is discriminated by its k l l + Gll being equal Kll). In this case matching of wave functions on the surface [2] gives no excitation of this Bloch function and the associated CP cannot manifest itself.…”
Section: Construction Of Bands and Resultsmentioning
confidence: 99%
“…The data on Ni are similar to the data on Cu because of the similarity of their upper states. Calculated dRldE curves were obtained applying the conducting Fourier approximation [6]. This approximation reduces the calculations to primitive band structure calculations with a sufficiently close mesh of k, along k , , = KlI + g rods of BZ and this enables very fast computations within a wide range of incident Kll.…”
Section: Experiments and Calculationsmentioning
confidence: 99%
See 2 more Smart Citations
“…The theoretical foundation for VLEED investigations is the matching approach [12,13,14], which links the elastic reflectivity R(E) to the properties of the Bloch waves excited in a crystal, including their dispersion. However, detailed band mapping from VLEED data was demonstrated only recently [15,16,17], using the no-absorption approximation. It has been found that an incident beam of energy E and parallel wave-vector component K significantly excites only so-called coupling bands.…”
Section: Introductionmentioning
confidence: 99%